Customer Data: Contemporary Issues of Privacy and Trust - Themistocleous, Christos (My University, 2018)
Customer information is essential for the survivability of organisations. Previous practices revolved around the unconsented acquisition and use of customer information, which is a matter currently being tackled by data protection initiatives in the UK, Central Europe and the USA. Imperative to the process of sustainable development and capacity building is the understanding of how customers perceive privacy, as well as what factors can alleviate disclosure concerns through reciprocal information exchanges and the instilment of trust. These key areas are examined in this chapter as they have the potential to sustainably streamline the delicate process of the accumulation, use and sharing of customer information.
Keywords: Marketing Management; Management